Lower-limb activity during the power serve in tennis: Effects of performance level - Girard, O.; Micallef, J. P.; Millet, G. P. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The aim of the present study was to investigate the differences in lower-limb activity during the tennis power serve between players of different performance levels.